Associations among high altitude, allergic rhinitis, and bronchial hyperreactivity - Oğhan, Fatih; Erdim, İbrahim (ENT Updates, 2017)
Allergic respiratory diseases are common public health problem. Although several treatment options, some of patients cannot manage to get satisfactory recovery. High altitude (HA) is shown as a natural additive and/or salvage therapy option for this patient group. We aimed to present the effect of HA on allergic rhinitis and bronchial hyperreactivity in company with literature.